의사면허 필기시험 제도의 성과와 과제 - 백상호; Baik, Sang-Ho (의학교육논단, 2013)
Since the establishment of the national medical licensing examination board in 1992, the medical licensing examination system has changed enormously and this has had a number of impacts on examination services. All those reforms were aimed at improving the relevance and reliability of the test. Several attempts of the testing system have appeared in the new examination service, and which have also brought about the changes in the medical school curriculum such as introducing integrated courses instead of traditional subjects, using test scores as a reference to the post-graduation selection test. Some examples of changes in the examination system are as follows: 1) choosing three integrated test subjects and outlines of their reference content instead of 15 academic subjects, 2) adjusting the ratio of multiple choice question items to focus more on the problem solving level, 3) introduction of 'one-best answer' single set and 'extended matching type items, 4) item construction based on real clinical cases and real clinical materials. Recently, a clinical skill test system has been introduced to measure examinees' basic clinical skills competencies. Despite continuing efforts, the examination system still has many issues remaining to be solved. These problems include the differential weighting of test items, appropriate threshold for passing, and practicality of pre-testing to stabilize the passing rate and avoid the hazards of newness and undesirably difficult test items.